Choice and voice: emerging questions of personalised professional learning. Issue 2 (4th May 2022) - Kennett, Daron William; Gardner, A.; Scott, L.; Patterson, M. S.; Zhang, L.; Carter, R. A.
ABSTRACT: Personalised professional learning (PPL) for teachers is increasingly seen as a route to improving student outcomes. The U.S. Every Student Succeeds Act (ESSA) legislation urges personalisation in learning for both students and educators, but states have yet to settle on shared definitions or approaches. Infrastructure such as microcredential and digital badge systems offer opportunities for PPL. Future research using Self Determination Theory and Organismic Integration Theory can yield better understanding of learner motivation vis-à-vis PPL, while the Universal Design for Learning (UDL) framework is a promising approach for effective learning design with PPL.